Morphological instability of a non-equilibrium ice-colloid interface - Peppin, S; Majumdar, A; Wettlaufer, J (2010)
We assess the morphological stability of a non-equilibrium ice-colloidal suspension interface, and apply the theory to bentonite clay. An experimentally convenient scaling is employed that takes advantage of the vanishing segregation coefficient at low freezing velocities, and when anisotropic kinetic effects are included, the interface is shown to be unstable to travelling waves. The potential for travelling-wave modes reveals a possible mechanism for the polygonal and spiral ice lenses observed in frozen clays. A weakly nonlinear analysis yields a long-wave evolution equation for the interface shape containing a new parameter related to the highly nonlinear liquidus curve in colloidal systems. We discuss the implications of these results for the frost susceptibility of soils and the fabrication of microtailored porous materials. © 2009 The Royal Society.